004 Vestibular event monitoring in the emergency department. (29th July 2019) - Nham, Benjamin; Reid, Nicole; Argaet, Emma; Young, Allison; Bein, Kendall; Halmagyi, Gabor M; Welgampola, Miriam S
Abstract : Introduction: Acute vertigo is often accompanied by ictal-nystagmus which may assist with diagnosis. We examine the merits of a structured assessment combined with vestibular event-monitoring in the Emergency Department (ED). Methods: We undertook a structured clinical assessment and video-nystagmography in 220 non-consecutive patients presenting to a public-hospital ED with acute vertigo, during a 10-month period. The records of 115 consecutive vertiginous patients who underwent standard-assessment were compared. Results: For the structured assessment group: 54% presented with acute vestibular syndrome (AVS), 24% with episodic spontaneous vertigo (EVS), and 20% with recurrent positional-vertigo (RPV). For AVS (n=119), most common diagnoses were vestibular neuritis (34%), stroke (34%) and vestibular migraine (13%). Nystagmus slow-phase velocity (SPV) for VN, stroke and VM were 11±5.5 o /s, 5.6±2.5 o /s, 5.4±5.9 o /s; Mean ipsilesional video-head impulse gains were 0.51±0.29, 0.89±0.20 and 0.96±0.13. For EVS(n=53), diagnoses included vestibular migraine (63%), Meniere's Disease (11%) and others (26%). Nystagmus SPV was 5.4±3.6 o /s, 7.6±6.3 o /s, 4.1±1.5 o /s. In RPV (n=43), common diagnoses were posterior-canal BPPV (66%), horizontal-canal BPPV (23%), migraine (7%). Positional nystagmus SPV profile showed Peak SPV of 42.5 o /s, 77.6 o /s, 20.64 o /s and Time-constants of 6.52s, 22.51s, 34.56s for Posterior-canal BPPV, Horizontal-canal BPPV and Atypical Positional-Vertigo. A final diagnosis was reached in 96% of patients. In the ED control group, only 77% were separated into spontaneous or positional-vertigo. A diagnosis was provided in 57% and was concordant with the history and examination in 34%. Conclusion: Vestibular event-monitoring and structured clinical assessment secured a diagnosis in 96% of cases compared with 34% for the control group, reinforcing its merit.